Diagnostic Utility of Cell Block and Conventional Cytology in Evaluation of Lymph Node Aspirates - Gupta, Sumiti; Ritu; Rathee, Pooja; Kumar, Davinder; Verma, Renuka; Singh, Sunita (Annals of Pathology and Laboratory Medicine, 2025)
Background: This study was conducted to assess the diagnostic utility of cell block and conventional cytology in the evaluation of lymph node aspirates. Methods: This was a one-year prospective study approved by the ethical committee of the institution and was carried at a tertiary care hospital, Pt B.D. Sharma, PGIMS, Rohtak. This study included 46 patients attending the cytology outpatient department who were referred for fine needle aspiration from other clinical departments. FNAC was performed without anaesthesia, and the aspirated material was flushed on slides and then fixed immediately. The remaining materials were processed into cell blocks followed by H&E staining. The collected data was analysed using SPSS version 20 (IBM SPSS Statistics Inc., Chicago, Illinois, USA) Windows software program. A p-value <0.05 was taken as significant. Results: The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of the combined cytosmear and cell block technique for cytopathological diagnosis were 100%, 75.8%, 78.59%, 100% and 85.39% respectively. The combined use of cytosmear and cell block led to increased diagnostic efficiency. Conclusion: The combined use of FNAC smear and cell block can be useful for establishing a more definitive cytopathologic diagnosis of lymphadenopathy. Compared with FNAC, it gives a more accurate diagnostic architecture and apparent histopathological features.